Understanding variation in management of early-onset neonatal sepsis in India: a vignette-based survey - Christina M Schumacher; Samuel McAleese; Tushar B Parikh; Basma Ouddi; Julia Johnson (BMJ Paediatrics Open)
Background Antibiotic use for early-onset neonatal sepsis (EONS) is common, but prolonged exposure can lead to poor outcomes. Laboratory capacity and infection prevention initiatives may impact antibiotic use for EONS in neonatal intensive care units. The objective of this study was to examine the influence of institutional capacity on antibiotic prescribing for EONS in India.Methods Between September 2023 and January 2024, we surveyed Indian paediatricians and neonatologists regarding institutional capacity and antibiotic prescribing practices for EONS. Five vignettes with varying maternal and infant risk profiles explored participants’ decision to initiate empiric antibiotics at birth and the timing of discontinuation of antibiotics in term and preterm infants at risk for EONS. Variation in reported initiation and discontinuation of empiric antibiotic use by institutional capacity and antimicrobial stewardship initiatives were assessed using logistic regression models.Results Of 317 respondents, most (91%) reported antimicrobial stewardship initiatives at their institution and 56% reported receiving blood culture results within 48 hours. Screening tests such as complete blood count and C reactive protein were used in 56%–67% of cases, and abnormal results led to longer courses with fewer than 10% of respondents discontinuing antibiotics by 72 hours. When controlling for infant and maternal characteristics, the adjusted OR of observing infants without empiric antibiotics at birth was 0.38 (95% CI 0.16 to 0.70) for participants without infection prevention initiatives and was 1.57 (95% CI 1.05 to 2.35) for participants with timely (<48 hours) reporting of blood culture results, respectively. Infection prevention initiatives and laboratory capacity were not associated with increased odds of early discontinuation of empiric antibiotics for EONS.Conclusions Infection prevention and laboratory capacity may decrease the initiation of empiric antibiotics but are not associated with early discontinuation of empiric antibiotics for EONS. The use of sepsis screening tests remains common in Indian neonates and requires additional study.